Expanding the OMOP Common Data Model to Support Perinatal Research in Network Studies - Abellan, Alicia; Burn, Edward; Trinh, Nhung T. H.; Burkard, Theresa; Callahan, Alison; Fernández‐Bertolín, Sergio; Hurley, Eimir; Rodriguez, Clara; Segundo, Elena; Morales, Daniel R.; M. E. Nordeng, Hedvig; Duarte‐Salles, Talita (Pharmacoepidemiology and drug safety, 2025)
ABSTRACT Objectives The Observational Medical Outcomes Partnership common data model (OMOP‐CDM) is a useful tool for large‐scale network analysis but currently lacks a structured approach to pregnancy episodes. We aimed to develop and implement a perinatal expansion for the OMOP‐CDM to facilitate perinatal network research. Methods We collaboratively developed a perinatal expansion with input from domain experts and stakeholders to reach consensus. The structure and vocabularies followed the OMOP‐CDM ontological framework principles. We tested the expansion using SIDIAP and Norwegian databases. We developed a diagnostics package for quality control assessment and conducted a descriptive analysis on the captured perinatal data mapped to the OMOP‐CDM. Results The perinatal expansion consists of a pregnancy table and an infant table, each with required and optional variables incorporated into standardized vocabularies. Quality assessment of the perinatal expansion table in SIDIAP and Norwegian databases demonstrated accurate capture of perinatal characteristics. Descriptive analysis measured the number of pregnancies (SIDIAP: 646 530; Norway: 746 671), pregnancy outcomes (e.g., 0.5% stillbirths in SIDIAP and 0.4% in Norway), gestational length (median [IQR] in days, SIDIAP: 273 [56–280]; Norway: 280 [273–286]), number of infants (Norway: 758 806), and birth weight (median [IQR] in grams, Norway: 3520 [3175–3860)], among other relevant variables. Discussion and Conclusion We developed and implemented a perinatal expansion that captures important variables for perinatal research and allows interoperability with existing tables in the OMOP‐CDM, which is expected to facilitate future network studies. The publicly available diagnostics package enables testing the implementation of the extension table and the quality and completeness of available data on pregnancy and pregnancy‐related outcomes in databases mapped to the OMOP CDM.